Design and control of a permanent magnet spherical wheel motor. Issue 6 (22nd July 2019) - Park, Junbo; Kim, Minki; Jang, Hyun Gyu; Jung, Dong Yun; Park, Jong Moon
Abstract : We present a permanent magnet–based spherical wheel motor that can be used in omnidirectional mobility applications. The proposed motor consists of a ball‐shaped rotor with a magnetic dipole and a hemispherical shell with circumferential air‐core coils attached to the outer surface acting as a stator. Based on the rotational symmetry of the rotor poles and stator coils, we are able to model the rotor poles and stator coils as dipoles. A simple physical model constructed based on a torque model enables fast numerical simulations of motor dynamics. Based on these numerical simulations, we test various control schemes that enable constant‐speed rotation along arbitrary axes with small rotational attitude error. Torque analysis reveals that the back electromotive force induced in the coils can be used to construct a control scheme that achieves the desired results. Numerical simulations of trajectories confirm that even without explicit methods for correcting the rotational attitude error, it is possible to drive the motor with a low attitude error (<5°) using the proposed control scheme.